A Combined Experimental and Theoretical Investigation of Oxidation Catalysis by cis-[VIV(O)(Cl/F)(N4)]+ Species Mimicking the Active Center of Metal-Enzymes - Papanikolaou, Michael G.; Simaioforidou, Anastasia V; Drouza, Chryssoula; Tsipis, Athanassios C.; Miras, Haralampos N.; Keramidas, Anastasios D.; Louloudi, Maria; Kabanos, Themistoklis A. (My University, 2022)
Reaction of VIVOCl2 with the nonplanar tetradentate N4 bis-quinoline ligands yielded four oxidovanadium(IV) compounds of the general formula cis-[VIV(O)(Cl)(N4)]Cl. Sequential treatment of the two nonmethylated N4 oxidovanadium(IV) compounds with KF and NaClO4 resulted in the isolation of the species with the general formula cis-[VIV(O)(F)(N4)]ClO4. In marked contrast, the methylated N4 oxidovanadium(IV) derivatives are inert toward KF reaction due to steric hindrance, as evidenced by EPR and theoretical calculations. The oxidovanadium(IV) compounds were characterized by single-crystal X-ray structure analysis, cw EPR spectroscopy, and magnetic susceptibility. The crystallographic characterization showed that the vanadium compounds have a highly distorted octahedral coordination environment and the d(VIV-F) = 1.834(1) Å is the shortest to be reported for (oxido)(fluorido)vanadium(IV) compounds. The experimental EPR parameters of the VIVO2+ species deviate from the ones calculated by the empirical additivity relationship and can be attributed to the axial donor atom trans to the oxido group and the distorted VIV coordination environment. The vanadium compounds act as catalysts toward alkane oxidation by aqueous H2O2 with moderate ΤΟΝ up to 293 and product yields of up to 29% (based on alkane); the vanadium(IV) is oxidized to vanadium(V), and the ligands remain bound to the vanadium atom during the catalysis, as determined by 51V and 1H NMR spectroscopies. The cw X-band EPR studies proved that the mechanism of the catalytic reaction is through hydroxyl radicals. The chloride substitution reaction in the cis-[VIV(O)(Cl)(N4)]+ species by fluoride and the mechanism of the alkane oxidation were studied by DFT calculations.
Keywords: Alkanes; Catalysis; Chlorides; Fluorides; Hydrogen Peroxide; Ligands; Vanadium; Vanadium Compounds